Porphyrin/Quinoidal‐Bithiophene‐Based Macrocycles and Their Dications: Template‐Free Synthesis and Global Aromaticity. Issue 6 (19th December 2019) - Ren, Longbin; Gopalakrishna, Tullimilli Y.; Park, In‐Hyeok; Han, Yi; Wu, Jishan
Abstract: We report the template‐free synthesis and characterization of a new type of porphyrin/quinoidal‐bithiophene‐based conjugated macrocycle. X‐ray crystallographic analysis of the dimer (2MC ) revealed a cyclophane‐like geometry with large dihedral angles between the porphyrin and the neighboring thiophene rings, and NMR measurements and theoretical calculations confirmed a localized aromatic character of the porphyrin/thiophene rings and quinoidal character of the bithiophene linkers. Restricted rotation of the thiophene rings linked to the porphyrin unit was observed by variable‐temperature NMR measurements. The dication (2MC 2+ ) adopts a chair‐shaped conformation to facilitate π‐electron delocalization around the whole macrocycle. As a result, the molecule is globally aromatic, with a dominant 54 π conjugation pathway. The trimer (3MC ) also shows localized aromatic character of porphyrin rings and conformational flexibility, but its dication (3MC 2+ ) is rigid and globally aromatic with a dominant 82 π conjugation pathway. Abstract : Adaptable porphyrin‐based macrocycles : Macrocycles containing aromatic porphyrin and quinoidal bithiophene units were synthesized by a template‐free method. The molecules adopted a distorted conformation with local aromaticity in the neutral state, but a more planar geometry with global aromaticity in the dication state (see picture).